2021
DOI: 10.1111/eje.12727
|View full text |Cite
|
Sign up to set email alerts
|

When e‐learning takes centre stage amid COVID‐19: Dental educators' perspectives and their future impacts

Abstract: Introduction The COVID‐19 pandemic has necessitated an unprecedented shift from face‐to‐face teaching to e‐learning. Previous surveys revealed the negative impact of COVID‐19 on dental education and the physical and psychological well‐being of dental students. This qualitative study aimed to investigate the perspectives of dental educators towards e‐learning during the pandemic and the impact of this experience on their future adoption of e‐learning. Materials and Methods Semi‐structured interviews with dental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…The same study [ 14 ] found that, although e-learning amid COVID-19 is satisfactory, conventional learning is more appropriate for clinics and laboratories among medial students. Educators agreed that, despite the challenges they face with e-learning during COVID-19 in engaging students and assessing their academic performance, they will integrate e-learning in their future education [ 15 ]. Toquero [ 16 ] called for innovative strategies to enhance the learning experience among students in these critical times.…”
Section: Literature Review and Hypothesis Buildingmentioning
confidence: 99%
“…The same study [ 14 ] found that, although e-learning amid COVID-19 is satisfactory, conventional learning is more appropriate for clinics and laboratories among medial students. Educators agreed that, despite the challenges they face with e-learning during COVID-19 in engaging students and assessing their academic performance, they will integrate e-learning in their future education [ 15 ]. Toquero [ 16 ] called for innovative strategies to enhance the learning experience among students in these critical times.…”
Section: Literature Review and Hypothesis Buildingmentioning
confidence: 99%
“…E-learning also offers ease of access to information with wider variety and greater quantity, optimising the learning process. Studies have shown that e-learning modalities are used widely by students outside of their formal curricula and by health professionals for continuing professional education, indicating that they appreciate this mode of learning (Dyrek et al, 2022, Escobar et al, 2022, Goh et al, 2022, Grundgeiger et al, 2022, Hulke et al, 2022. E-learning is also designed to accommodate student needs with reduced costs of labour, fast delivery, scalability, and consistency of teaching in the face of limited availability of instructors.…”
Section: Discussionmentioning
confidence: 99%
“…Error rates tend to increase with more complex practical procedures (Balasubramaniam et al, 2018, Barakat et al, 2022, Bastos et al, 2022, Bock et al, 2021. Since University education provides only theoretical and practical skills, major innovations such as the introduction of endodontic tooth models like, 3-d printed plastic acrylic models and the incorporation of media into teaching have advanced dental education (Connolly, 2022, Dyrek et al, 2022, Escobar et al, 2022, Goh et al, 2022, Grundgeiger et al, 2022, Hulke et al, 2022. Studies assessing these teaching styles suggest many bene ts, but e-learning in isolation has limitations compared to F2F and/or hybrid teaching methods (Maqbool et al, 2022, Martinez-Melo et al, 2022, Mladenovic et al, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Since simulation‐based education and practical motor‐skill training are imperative for dental education, the obligatory shift in teaching modalities from traditional to online learning was a critical challenge for dental educators and students alike 4 . The shift was abrupt without prior training and preparation, and immediate adaptation to the new situation was essential.…”
Section: Introductionmentioning
confidence: 99%